Determination of the half-life of circulating leptin in the mouse - Burnett, L C; Skowronski, A A; Rausch, R; LeDuc, C A; Leibel, R L (International Journal of Obesity, 2017)
Background: The adipokine hormone, leptin, is a major component of body weight homeostasis. Numerous studies have been performed administering recombinant mouse leptin as an experimental reagent; however, the half-life of circulating leptin following exogenous administration of recombinant mouse leptin has not been carefully evaluated. Methods: Exogenous leptin was administered (3 mg leptin per kg body weight) to 10-week-old fasted non-obese male mice and plasma was serially collected at seven time points; plasma leptin concentration was measured by enzyme-linked immunosorbent assay at each time point to estimate the circulating half-life of mouse leptin. Results: Under the physiological circumstances tested, the half-life of mouse leptin was 40.2 (±2.2) min. Circulating leptin concentrations up to 1 h following exogenous leptin administration were 170-fold higher than endogenous levels at fasting. Conclusions: The half-life of mouse leptin was determined to be 40.2 min. These results should be useful in planning and interpreting experiments employing exogenous leptin. The unphysiological elevations in circulating leptin resulting from widely used dosing regimens for exogenous leptin are likely to confound inferences regarding some aspects of the hormone’s clinical biology.